Molecular cloning of a translocation breakpoint hotspot in 22q11 - Kurahashi, Hiroki; Inagaki, Hidehito; Hosoba, Eriko; Kato, Takema; Ohye, Tamae; Kogo, Hiroshi; Emanuel, Beverly S. (Genome Research, 2007)
It has been well documented that 22q11 contains one of the most rearrangement-prone sites in the human genome, where the breakpoints of a number of constitutional translocations cluster. This breakage-sensitive region is located within one of the remaining unclonable gaps from the human genome project, suggestive of a specific sequence recalcitrant to cloning. In this study, we cloned a part of this gap and identified a novel 595-bp palindromic AT-rich repeat (PATRR). To date we have identified three translocation-associated PATRRs. They have common characteristics: (1) they are AT-rich nearly perfect palindromes, which are several hundred base pairs in length; (2) they possess non-AT-rich regions at both ends of the PATRR; (3) they display another nearby AT-rich region on one side of the PATRR. All of these features imply a potential for DNA secondary structure. Sequence analysis of unrelated individuals indicates no major size polymorphism, but shows minor nucleotide polymorphisms among individuals and cis-morphisms between the proximal and distal arms. Breakpoint analysis of various translocations indicates that double-strand-breakage (DSB) occurs at the center of the palindrome, often accompanied by a small symmetric deletion at the center. The breakpoints share only a small number of identical nucleotides between partner chromosomes. Taken together, these features imply that the DSBs are repaired through nonhomologous end joining or single-strand annealing rather than a homologous recombination pathway. All of these results support a previously proposed paradigm that unusual DNA secondary structure plays a role in the mechanism by which palindrome-mediated translocations occur.